Distribution of the cattle ticks from mid hills to plains of Nepal - Dhital, Bigya; Shrestha, Sulav; Kaphle, Krishna; Pudasaini, Rameshwor (Journal of Agriculture and Natural Resources, 2018)
Ticks cause serious economic losses in livestock production worldwide. A study was conducted in 2017/18 to determine the abundance of tick population on different geographical regions and body parts of cattle. Three study sites were taken from mid hill, inner terai and terai region of Nepal. A total of 45 dairy cattle (15 from each region) were included randomly for the study. Regarding the distribution of ticks in cattle body part, higher number of ticks were recorded on dewlap (38.61%) followed by perineum and udder (25.10%), ear base (15.06%), tail base (9.07%), abdomen (7.34%) and withers (4.83%). Similarly, highest numbers of ticks were recorded in Chitwan (19.46 ticks on an average) cattle followed by Dang (9.13 ticks on an average) and least in Lamjung (5.73 ticks on an average) cattle. This result indicates that higher tick infestation was found in warm, moist, hidden sites with good vascular supply and thin skin in cattle body. Similarly, more tick were recorded in cattle keeping with poor animal husbandry practices.